PENGARUH LITERASI KEUANGAN, TEKNOLOGI FINANSIAL SYARIAH (FINTECH SYARIAH), DAN TINGKAT PEMBIAYAAN TERHADAP KINERJA UMKM KOTA PALEMBANG - Susanto, Muhammad Habibi; Lemiyana, Lemiyana; Pamuji, Pamuji (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
This study aims to examine the influence of financial literacy, Islamic financial technology (Islamic fintech), and the level of financing on the performance of MSMEs in Palembang City. This research employs a quantitative research method. The data used in this study are primary data obtained through the distribution of 96 questionnaires using the Lemeshow sampling technique. The analytical method applied is multiple linear regression analysis, with data processing conducted using SPSS version 26. The results of the study show that, partially, financial literacy has a positive and significant influence on the performance of MSMEs in Palembang City. Islamic financial technology (Islamic fintech) has a negative and insignificant influence on the performance of MSMEs in Palembang City. The level of financing also has a negative and insignificant influence on the performance of MSMEs in Palembang City. However, simultaneously, the three variables financial literacy, Islamic financial technology (Islamic fintech), and the level of financing have a positive and significant influence on the performance of MSMEs in Palembang City.